Do Women Fare Worse When Men Are Around? Quasi-Experimental Evidence - Marcela Gomez-Ruiz; María Cervini-Plá; Xavier Ramos (Institute of Labor Economics (IZA), 2024)
We investigate the impact of a change in the gender composition of the pool of candidates on the academic performance of women in an entrance exam. We use data from a natural experiment that altered the gender composition of the candidates for a nation-wide admission exam to a coding educational program. Our identification strategy exploits the fact that both men and women were accepted for the admission exam in all years except for 2019, when only women were allowed to take it. Our results reveal that in the absence of men, women exhibit enhanced performance, particularly in subjects where men do traditionally better, such as mathematics and logical reasoning. Conversely, we observe no significant effects in verbal tasks, where men do not typically outperform. The improvement in performance stems from both increased attempts at questions and a higher rate of correct answers. Women improve their academic performance by exerting greater effort when men are not present. Our findings are consistent with the hypothesis that the stereotype threat is deactivated in the absence of men, highlighting the nuanced impact of gender composition on women's performance in high-stakes exams.
Keywords: I20; I24; J16; J24; 330; gender; performance; effort; stereotype threat; competition